A multicentered, randomized, double-blind, parallel-controlled clinical trial on the homocysteine and blood pressure-lowering effects of amlodipine-folic acid versus amlodipine among H-type hypertensive patients intolerant to ACEI: principles and methods. Issue 3 (14th December 2022) - Huang, Xiao; Li, Yan; Li, Ping; Cheng, Zaihua; Fu, Ling; Ding, Congcong; Wang, Zhirong; Song, Demin; Yao, Chen; Chen, Guangliang; Cui, Yimin; Wang, Xiaobin; et al.
Abstract : Background: Hypertension is the most important modifiable risk factor for cardiovascular disease (CVD) morbidity and mortality. Elevated plasma total homocysteine (tHcy) coupled with hypertension can synergistically increase the risk for CVD and is highly prevalent in the Chinese population. The China Stroke Primary Prevention Trial has shown the efficacy of taking a daily enalapril-FA tablet in treating hypertension and HHcy. However, a substantial portion of patients cannot tolerate enalapril, an angiotensin-converting enzyme inhibitor (ACEI). The Precision Amlodipine-folic acid Trial to lower tHcy (ClinicalTrials.gov Identifier: NCT01956786) aimed to evaluate whether amlodipine combined with folic acid treatment is more efficacious than amlodipine alone in lowering plasma tHcy and blood pressure (BP) among Chinese patients with hypertension with HHcy and intolerance to ACEI. Methods: This was a multicentered, randomized, double-blind, parallel-controlled clinical trial conducted from December 19, 2013, to March 6, 2014, in 4 study centers across China (Shanghai, Nanchang, Xuzhou, and Anqing). Eligible participants who had mild to moderate hypertension were men and women aged 18 to 75 years, hyperhomocysteinemia and intolerant to ACEI. Eligible patients were randomly assigned in a 1:1:1 ratio to receive either an amlodipine 5 mg and FA 0.4 mg tablet daily (A group); or an amlodipine 5 mg and FA 0.8 mg tablet daily (B group); or an amlodipine 5 mg tablet daily (C group, control group) for a total of 8 weeks. The primary endpoints were tHcy-lowering and BP assessed at 2, 4, 6, and 8 weeks. Planned analyses included intent to treat and per protocol set, and multivariable logistic and linear regression models were used to evaluate the efficacy of amlodipine combined with FA in reducing tHcy and BP. Results: A total of 505 participants were enrolled in the screening period; of those, 458 entered the run-in period, and of those, 360 eligible participants were randomized to one of the 3 treatment groups. Overall, 31.3% of participants were male ( n = 110), with a mean age of 63.2 (SD: 6.2) years. The randomization was successful as demonstrated by the well-balanced distribution of baseline characteristics across the 3 groups. Conclusions: This is the first trial of its kind to inform the clinical management of patients with hypertension, HHcy and intolerant to ACEI. The rationale and methods of the trial are introduced in this article, which lays a foundation for subsequent publications.